2018
DOI: 10.1563/aaid-joi-d-16-00122
|View full text |Cite
|
Sign up to set email alerts
|

Peri-implantitis: A Comprehensive Overview of Systematic Reviews

Abstract: The objective of this systematic review was to perform a comprehensive overview of systematic reviews and meta-analyses pertaining to peri-implantitis in humans, including the prevalence and incidence, the diagnostic findings, microbial findings, effects of systemic diseases, and treatment of peri-implantitis. Electronic databases were searched for systematic reviews and meta-analyses of peri-implantitis. In view of the limitations of the included systematic reviews, the outcome of this overview suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
2
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 54 publications
1
77
2
11
Order By: Relevance
“…25,26 The present study found that MBL did not differ significantly with the presence of diabetes, although there was a tendency for MBL to decrease in patients with diabetes. 25,26 The present study found that MBL did not differ significantly with the presence of diabetes, although there was a tendency for MBL to decrease in patients with diabetes.…”
Section: Resultscontrasting
confidence: 50%
See 1 more Smart Citation
“…25,26 The present study found that MBL did not differ significantly with the presence of diabetes, although there was a tendency for MBL to decrease in patients with diabetes. 25,26 The present study found that MBL did not differ significantly with the presence of diabetes, although there was a tendency for MBL to decrease in patients with diabetes.…”
Section: Resultscontrasting
confidence: 50%
“…29 systematic review concluded that submerged implants showed significantly more MBL than nonsubmerged implants, but the difference was negligible in clinical practice. 25 In conclusion, dental implants with a higher abutment might show less MBL. Smoking is considered a risk factor for peri-implantitis, 26 and so that the effects of abutment height on MBL could be confounded by the influence of smoking.…”
Section: Resultsmentioning
confidence: 87%
“…It has been reported that complications in bone mineral metabolism are often manifested in patients with CKD compared with individuals without CKD. [33][34][35] We hypothesize that soft-tissue inflammation and CBL are significantly higher around adjacent implants placed in type-2 diabetic patients with other systemic diseases than patients with type-2 diabetes alone. 32 Similarly, a higher CBL around dental implants has been reported in patients with AIDS, CVD, and liver diseases compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated quality assessments in SRs regarding periodontal treatment and dental implant treatments . Ting et al conducted a comprehensive overview of SRs regarding peri‐implantitis focusing on not only treatments, but also prevalence, etiology, and diagnosis. Though they successfully summarized evidence obtained from SRs and showed clinical suggestions, methodological assessments and assessment of the risk of bias were not conducted.…”
Section: Introductionmentioning
confidence: 99%